Genetic data for 15 STR loci in a Kadazan-Dusun population from East Malaysia - Kee, B.P.; Lian, L.H.; Lee, P.C.; Lai, T.X.; Chua, K.H. (2011)
Allele frequencies of 15 short tandem repeat (STR) loci, namely D5S818, D7S820, D13S317, D16S539, TH01, TPOX, Penta D, Penta E, D3S1358, D8S1179, D18S51, D21S11, CSF1PO, vWA, and FGA, were determined for 154 individuals from the Kadazan-Dusun tribe, an indigenous population of East Malaysia. All loci were amplified by polymerase chain reaction, using the Powerplex 16 system. Alleles were typed using a gene analyzer and the Genemapper ID software. Various statistical parameters were calculated and the combined power of discrimination for the 15 loci in the population was calculated as 0.999999999999999. These loci are thus, informative and can be used effectively in forensic and genetic studies of this indigenous population.